Implementation of the Food Estate in Merauke: Legal Review and Protection of Indigenous Peoples’ Rights - Bagus Yudha Prawira; Djoko Andoko; Diah Ayu Permatasari; Edy Supriyadi (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
This study aims This study aims to analyze the implementation of the Food Estate program in Merauke, Papua, which is part of Indonesia’s National Strategic Projects aimed at strengthening food security. However, its execution has raised legal, environmental, and human rights concerns, particularly regarding indigenous peoples’ rights. Using a qualitative-juridical approach, this study examines the program’s alignment with Indonesia’s legal framework, including the Basic Agrarian Law, Human Rights Law, Environmental Law, Village Law, and Papua’s Special Autonomy Law. The findings indicate systemic neglect of customary land right, the principle of Free, Prior, and FPIC, and meaningful community participation. The study also identifies serious ecological impacts, militarization of land acquisition, and practices of food colonization. It concludes by recommending stronger legal enforcement, recognition of indigenous land rights, demilitarization of development processes, and policy designs that prioritize local food sovereignty.